THE SIGNIFICANCE OF C‑REACTIVE PROTEIN IN SYSTEMIC LUPUS ERYTHEMATOSUS - S. M. Noskov; O. A. Vasilevskaja; T. S. Noskova; N. A. Arzimanova (Klinicist)
It is believed that the concentration of C‑reactive protein (CRP) significantly increases in acute forms of systemic lupus erythematosus (SLE). A moderate increase of CRP levels in patients with stable disease progression reflects the low‑grade chronic inflammation in the vascular wall and the development of subclinical atherosclerosis. The article presents data showing that increased CRP levels in SLE patients is not statistically related with disease activity and cardiovascular risk as well as the level of interleykin‑6. Patients with lupus nephritis have lower CRP concentration compared to patients without renal disease and CRP concentration depends on proteinuria and hypoalbuminemia.